A circular cylinder in the main-channel/floodplain interface of a compound channel: effect of the shear flow on drag and lift. Issue 3 (15th April 2020) - Gymnopoulos, Miltiadis; Ricardo, Ana M.; Alves, Elsa; Ferreira, Rui M.L.
Abstract : The interface between the main channel and the floodplain of a compound channel is often populated by trees or buildings that normally remain emergent during floods. This study investigates how drag on an emergent cylinder is affected by the shear flow that develops at the interface. The experimental set-up features a circular cylinder at the interface of a straight compound channel under uniform flow conditions. The integral form of the equation of conservation of momentum was used to calculate the magnitude and direction of the time-averaged drag force per unit submerged-length of the cylinder. All terms were experimentally determined, except for those associated with fluid interaction with the cylinder. The same method was also applied to a cylinder under symmetrical flow conditions. It is concluded that the existence of the shear layer leads to an asymmetrical drag force and to a reduced drag coefficient.